Pengaruh Aktivitas Bersepeda terhadap Semangat Mengajar Guru di Pondok Pesantren Darullughah Wadda’wah Bangil - Marzuqi Marzuqi; Badrus Shalih (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Teachers’ physical health is a crucial factor that affects professional performance, particularly in maintaining optimal teaching enthusiasm in highly demanding educational environments such as pesantren. This study aimed to examine the effect of cycling activity on teachers’ teaching enthusiasm at Pondok Pesantren Darullughah Wadda’wah Bangil. This study used a correlational quantitative approach involving 18 teachers as the sample, selected through simple random sampling. Data were collected using a five-point Likert scale-based questionnaire measuring the variables of cycling activity and teaching enthusiasm, and were then analyzed using simple linear regression. The results showed that teachers’ cycling activity was in the moderate category (M = 3.60), while teachers’ teaching enthusiasm was in the high category (M = 4.10). The hypothesis testing results showed that cycling activity had a significant effect on teachers’ teaching enthusiasm, with a significance value of 0.000, a β coefficient of 0.775, and an R² value of 0.600. These findings indicate that cycling activity was able to explain 60% of the variance in teachers’ teaching enthusiasm. The conclusion of this study confirms that physical activity, particularly cycling, plays an important role in supporting teachers’ psychological condition and pedagogical effectiveness. The implications of this study indicate the need to develop health programs based on physical activity in pesantren environments as a sustainable strategy to improve educational quality.